Project Based Learning (Pjbl) dalam Proses Pembelajaran Daring pada Materi Hukum Bernoulli Menggunakan Botol Bekas - Sutejo Sutejo; Eka Yuli Sari Asmawati; Lakon Wahono; Nyoto Suseno (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
Covid-19 has an impact on education. In order to maintain the quality of learning, online mode learning innovation is carried out with the application of project based learning through experiments in the application of Bernoulli's Law on used bottle leaks. Online learning at SMAN 1 Metro usually uses Problem Based Learning. In this study will be used PjBl to increase the creativity of students. This research aims to explore students' ability in problem solving in dynamic fluid concepts. This type of research is quantitative with a Quasi Experimental approach, and the design used is Nonequivalent Group Design. The subject of the study was Sma N 1 Metro in class XI IPA which numbered 67 students. The analysis method uses the N-Gain Test and the different tests between the two sample groups. Results: N-Gain in experimental class by 65.74% and in control class by 25.04%. Based on hypothesis tests, it was found that the effect of applying madel project based learning in improving student learning outcomes in Bernoulli Law material. Project based learning model in online learning is also effective in developing 4Cs.